Value, Transcendence and Cultural Death in Hermann Brochʼs Thinking - Natucci Cortazzo, Julián (Revista de Filología Alemana, 2025)
Hermann Broch is a little-known author in the philosophical field. My purpose in this paper is to make his thoughts known through his philosophical essays. In these writings, two of the most important concerns of the Austrian philosopher and novelist are the decline of Western culture and the crisis of values of our time, a crisis that is due to the loss of contact with the transcendent. Through his concept of "degradation of values" (Wertzerfall) and his critique of positivist culture, I will present an interpretation of Broch’s philosophy in a Platonic-medieval and metaphysical-existential key, considering some authors of special relevance in his work. Our author, in order to save philosophy, proposes a vindication of the Middle Ages and a critique of modernity that becomes more pressing as the years go by. For Broch, the materialism must be transmuted into a kind of innovative spiritualism.